1999
DOI: 10.1121/1.426831
|View full text |Cite
|
Sign up to set email alerts
|

Sensor coupling in acoustic media using reciprocity

Abstract: In this paper the coupling of a sensor to an acoustic medium is discussed. Based on the acoustic reciprocity theorem, an expression is derived for the motion of the sensor as a function of the undisturbed motion of the embedding medium. What is special here is that the sensor is the scattering object. The sensor coupling is affected by two factors: the ratio of the density of the sensor and of the embedding medium (ground), and a frequency-dependent factor depending on the geometry of the sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Tan (1987) concludes that, for perfect coupling, the density of the measuring device has to be the same as the density of the medium. Vos et al (1999) suggest that this condition may not be sufficient. They make a distinction between contact coupling, which is perfect if the sensor follows exactly the motions of the surrounding medium (perfect contact between sensor and surroundings), and interaction coupling, which is perfect if the motion of the medium is not influenced by the presence of the sensor (sensor as a scatterer).…”
Section: Coupling Issuesmentioning
confidence: 88%
“…Tan (1987) concludes that, for perfect coupling, the density of the measuring device has to be the same as the density of the medium. Vos et al (1999) suggest that this condition may not be sufficient. They make a distinction between contact coupling, which is perfect if the sensor follows exactly the motions of the surrounding medium (perfect contact between sensor and surroundings), and interaction coupling, which is perfect if the motion of the medium is not influenced by the presence of the sensor (sensor as a scatterer).…”
Section: Coupling Issuesmentioning
confidence: 88%
“…Tan (1987) considered the effect of the spikes firstly who used the Betti-Rayleigh reciprocal theory to study the coupling resonant system effect when the spike was well-coupled with the ground [12] . Vos et al (1995Vos et al ( , 1999 divided the geophone coupling into two parts. One was the "interaction coupling" when the spike was well-coupled with the ground, and the other is "contact coupling" when the spike was not well-coupled with the ground.…”
Section: Introductionmentioning
confidence: 99%
“…One was the "interaction coupling" when the spike was well-coupled with the ground, and the other is "contact coupling" when the spike was not well-coupled with the ground. Aiming at the problem of the "interaction coupling", Vos studied the coupling transmission law between the columned or rectangular spike and ground based on acoustic theory of reciprocity and found that "interaction coupling" would make the difference obviously between the geophone velocity and the truly ground velocity without geophone even if the spike was well-coupled with the ground [13,14] . But the conclusions based on the acoustic theory of reciprocity were of great application limitation to the seismic waves.…”
Section: Introductionmentioning
confidence: 99%
“…And the theoretical models of geophone-ground coupling include "interaction coupling model", "stack effect model" and "2-DOF model". Using "Interaction coupling model", some scholars had studied the coupling transmission law when the spike was well-coupled with the ground and the results showed that "interaction coupling" would make the difference obviously between the geophone velocity and the truly ground velocity without geophone even if the spike was well-coupled with the ground (Tan, 1987;Vos, 1995Vos, , 1999Rademakers, 1996;Drijkoningen, 2006). Jinxi Xu et al (1999) raised the "stack effect" theoretical model and found that the "stack effect" caused by the length of the spike is equivalent to a low-pass filter.…”
Section: Introductionmentioning
confidence: 99%